Wind Turbines Advances and Challenges in Design, Manufacture and Operation - Maalawi, Karam (IntechOpen, 2022)
Much research is being conducted to develop larger wind turbines, both onshore and offshore, to decarbonize electricity grid systems through the exploitation of wind power. This book presents advances and challenges in the design, manufacture, and operation of wind turbines. The main topics addressed include the basic aspects of wind turbine design, offshore wind industry and floating wind turbines, wind measurement and forecasting models, design and manufacturing of rotor blades, manufacture of power transmission bearings, and challenges in control strategies and computational aerodynamics.